(untitled) (L’architettura delle città - The Journal of the Scientific Society Ludovico Quaroni, 2025)
Buildings used as seats for the representatives of local communities in the Middle Ages were (and often continue to be) a key element of the urban landscape as well as of cities’ identity. The phenomenon mainly involved central-northern Italy. The analysis of mediaeval municipalities necessitates an investigation of the relationship between public space and municipal buildings. The historiography has primarily focused on the north of Italy, where there is a strong communal presence. Numerous studies conducted in the Lombardy region and intriguing publications released in Tuscany serve as a foundation for historical-architectural analyses of communal buildings. There is a lack of research on municipal palaces in central Italy. In this historiographical context, it’s intriguing to investigate the territorial declinations of these and their relationship with the urban context. The palaces, built since the late 11th century, delineate the skyline of the city, occupying a prominent position. In this paper, I aim to analyse three different case studies in Umbria and Latium: Bevagna, Assisi, and Priverno.